1977
DOI: 10.1111/j.1744-7348.1977.tb00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of potato tuber resistance to infection by Phytophthora infestans

Abstract: Eyes and lenticeis on tubers of cvs King Edward, Record, M a r i s Peer andMajestic gradually became more resistant to infection by Phytqphthwa infestans as the growing season progressed. Lenticels of Record and Majestic, and eyes of Maris Peer and Majestic were more resistant than those of King Edward. Differences in resistance between cultivars were apparent at all concentrations of inoculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Some studies have shown that resistance to initial infection of potato eyes and lenticels of tubers gradually increased as the growing season progressed and the tubers matured (Lapwood 1967;Walmsley-Woodward and Lewis 1977;Malcolmson 1981;Stewart et al 1983;Bjor 1987). Grinberger et al (1995) further reported that tuber blight incidence and severity were strongly affected by tuber age: an increase in tuber resistance to blight during vegetation (tested between 48 and 95 days after planting) and in storage (tested between 118 and 208 days after planting) was observed.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have shown that resistance to initial infection of potato eyes and lenticels of tubers gradually increased as the growing season progressed and the tubers matured (Lapwood 1967;Walmsley-Woodward and Lewis 1977;Malcolmson 1981;Stewart et al 1983;Bjor 1987). Grinberger et al (1995) further reported that tuber blight incidence and severity were strongly affected by tuber age: an increase in tuber resistance to blight during vegetation (tested between 48 and 95 days after planting) and in storage (tested between 118 and 208 days after planting) was observed.…”
Section: Discussionmentioning
confidence: 92%
“…The results reported here show that immature tubers are more prone than mature tubers to infection by P. infestans during bulk washing. Walmsley-Woodward & Lewis (1977) found that the resistance of eyes and lenticels of tubers of several cultivars to infection by P. infestans, lifted at intervals of two weeks from mid-July onwards, Research 40 (1997) gradually increased as the tubers matured. It follows therefore that washing stocks of immature tubers before mature tubers may reduce the spread of tuber blight if the wash water is not changed between stocks.…”
Section: Discussionmentioning
confidence: 97%
“…Due to prolonged infection risk from partly infected foliage, tuber resistance is regarded as being particularly relevant in cultivars resistant to P. infestans . There are reports that P. infestans can also enter tubers via stolons (Zeck, 1957;Walmsley-Woodward & Lewis, 1977). Later their resistance decreases, but rises again with advancing tuber maturity.…”
Section: Tuber Resistance and The Potato -P Infestans Pathosystemmentioning
confidence: 99%